Plastic structures for diverse substrates: A revisit of human ABC transporters. Issue 10 (26th August 2022) - Hou, Wen‐Tao; Xu, Da; Wang, Liang; Chen, Yu; Chen, Zhi‐Peng; Zhou, Cong‐Zhao; Chen, Yuxing
Abstract: ATP‐binding cassette (ABC) superfamily is one of the largest groups of primary active transporters that could be found in all kingdoms of life from bacteria to humans. In humans, ABC transporters can selectively transport a wide spectrum of substrates across membranes, thus playing a pivotal role in multiple physiological processes. In addition, due to the ability of exporting clinic therapeutics, some ABC transporters were originally termed multidrug resistance proteins. Increasing investigations of human ABC transporters in recent years have provided abundant information for elucidating their structural features, based on the structures at distinct states in a transport cycle. This review focuses on the recent progress in human ABC structural analyses, substrate binding specificities, and translocation mechanisms. We dedicate to summarize the common features of human ABC transporters in different subfamilies, and to discuss the possibility to apply the fast‐developing techniques, such as cryogenic electron microscopy, and artificial intelligence‐assisted structure prediction, for future studies.